Apocrypha Hiberniae, II: Apocalyptica, 1: In Tenga Bithnua—The Ever-new Tongue. Edited by John Carey - Stancliffe, Clare (The journal of theological studies, 2012)
The Ever-new Tongue is an intriguing text, largely in Old Irish of the ninth or tenth centuries, and remaining popular thereafter in Ireland, with a second recension dating from the later Middle Ages. In part, this may be due to its evocative way of putting things. For instance, the depths of hell are conveyed by telling ‘that even though the bird which is swiftest and strongest in flight should set out, it would scarcely reach its bottom at the end of a thousand years’.